(3OjhGf HTGQs - (3HTGQ Hf HQO GdYbjdj, CHh eYGP,J (B167 (3g` s
(3BNQgG (B:s
(3jfJgi Edi MQa GdQGA s
(3JfbU YOI hQbGJ ef GdhSWs
(3eUhQ Yf fSNI GdSjO eMeO GdWGgQ Hf YGThQ HJhfSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B52s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B457 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs